(3GdJYGdjes - (3Sgd Hf HTQ Hf MHjH Hf gGfj, CHh YKeGf GdESQGFjdj,J (B235 (3g` s
(3ChdgG (B:s
(3Ef WHGFY GdbdhH ebSheI Ydi GdHQhL GdCKfi YTQ hGdSHYI GdchGcH aef GdHQhL SJI PchQ , hSJI EfGK aChdgG , hgh HQL GdMed , PcQ fgGQi hefgG eSJbjeI GdWdhY , hefgG eYhLI GdWdhY s
(3BNQgG (B:s
(3abO jfRd HgPG GdPi jNGa abO Ce , aGfXQ Edi UGMH GdWGdY s
(3Vef eLehY , JQJjHgG (B: (3ef U (B176 - (3U(B229s
(3HgG WeS hYOe hVhMHBNQgG KdGK hQbGJ ai (B" (3SgGe GdchGcH GdSHYI (B"s
(3cJHJ HNW eZGjQs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B142 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B283s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B252 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B396 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs